If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4v + 8 = 6(v + 4) Reorder the terms: 8 + 4v = 6(v + 4) Reorder the terms: 8 + 4v = 6(4 + v) 8 + 4v = (4 * 6 + v * 6) 8 + 4v = (24 + 6v) Solving 8 + 4v = 24 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 8 + 4v + -6v = 24 + 6v + -6v Combine like terms: 4v + -6v = -2v 8 + -2v = 24 + 6v + -6v Combine like terms: 6v + -6v = 0 8 + -2v = 24 + 0 8 + -2v = 24 Add '-8' to each side of the equation. 8 + -8 + -2v = 24 + -8 Combine like terms: 8 + -8 = 0 0 + -2v = 24 + -8 -2v = 24 + -8 Combine like terms: 24 + -8 = 16 -2v = 16 Divide each side by '-2'. v = -8 Simplifying v = -8
| 114=39.95x | | 12x-6-6x-8=4-3x | | 5(3x-10)-5x=-15 | | 39=-3v | | 21x+3d=45 | | 7y^2-y+2=0 | | 19y-10=11y-2 | | 6.4=1.3-0.7y | | X+67+x+127=180 | | 36-7b=-3b(8b+5) | | 2y-3y+5y=42 | | 5h+4=3h+8 | | -54=9x | | 5m+4=-26 | | X^2/x-5 | | 5h+4=h+8 | | 11=x-12 | | 88+2x+62=2x+26 | | 4/(x-2)=6 | | 1.1x-3x=-34.3 | | 12-r=-8 | | 26=(5-x) | | -2(7u-2)+3u=1+2(2u-1) | | 40=2(x-4) | | -2=n+(-17) | | -5+.25c=15 | | 2x^2+3x+8=3x-10 | | 6x-1=133 | | v-(-10)=17 | | 20+8x-88=-12 | | 4s^3+12s^2-64s-192=0 | | 4(3x+10)=100 |